Vibration attenuation of a propulsion shafting system by electromagnetic forces: Static thrust force balance and harmonic vibration suppression. (1st November 2022) - Xie, Xiling; He, Peitao; Wu, Di; Zhang, Zhiyi
Graphical abstract: Highlights: An active control scenario is proposed to suppress the vibration of a shafting system. The static force balance and the harmonic vibration suppression are combined. The longitudinal electromagnetic constraint can balance the static thrust force. The electromagnetic actuators can suppress the harmonic vibration of the bearing pedestal. The effectiveness of the proposed active control scenario is verified by experiments. Abstract: Suppressing the vibration of the thrust bearing and its transmission in a shafting system induced by the thrust force is an important measure to reduce low-frequency vibration and sound radiation. However, it is difficult to attenuate low-frequency vibration transmission from the shaft to the hull under the high-speed and heavy-load condition. An active control scenario is proposed to suppress the longitudinal vibration of the thrust bearing and its pedestal, in which an electromagnetic constraint is applied to balance the static thrust force while two inertial electromagnetic actuators are used to suppress the harmonic vibration of the bearing pedestal. The dynamic model of a shaft-foundation system with electromagnetic control forces is established on the basis of the modified Ritz method. A longitudinal position control method to balance the thrust force is built and the performance of position control and vibration attenuation is evaluated. The feasibility of the longitudinal vibration control of the bearing pedestal is analyzed, and the effectiveness of the proposed scenario for longitudinal vibration transmission attenuation is evaluated by combining the longitudinal position control of the shaft with the harmonic vibration suppression of the bearing pedestal. Simulations and experiments demonstrate that the proposed active control scenario is effective in longitudinal position adjustment and vibration attenuation.